Self-administration of a questionnaire on chest pain and intermittent claudication. Issue 1 (March 1977) - Rose, G; McCartney, P; Reid, D D
Abstract : A total of 18 403 men aged between 40 and 64 years took part in a screening examination which included a self-administered version of the London School of Hygiene questionnaire on chest pain and intermittent claudication. The yield of positives for "angina" and "history of possible infarction" was about twice as high as with interviewers, but the positive groups obtained by the two techniques differed little in their association with electrocardiographic findings or in their ability to predict five-year coronary mortality risk. This risk ranged from 0-9% in men negative to questionnaire and electrocardiograms (ECG), to 4-3% for those with positive ECG but no symptoms, 4-5% for those with angina and negative ECG, up to 16% for those with angina and positive ECG. The self-administered version of this questionnaire provides a simple and convenient means of identifying individuals with a high risk of major coronary heart disease.